“It is you who must be translated”: Translational Immortality and Mark Strand’s The Monument - Washbourne, Kelly (TTR)

(untitled) (Association canadienne de traductologie, 2022)
This study primarily surveys one work, Mark Strand’s The Monument (1978), though it is also a glimpse into translational immortality and authors’ relationships to their own afterlife, their legacy, and their (im)mortality. We will turn to other fictional translation scenarios in Strand’s work, and ideas emerging from interviews, but our analysis will focus largely on the ways the text at hand represents author-translator relations, the self in translation, including its intertextuality, translational immortality, and the notion of monumentality in the verbal arts.